Methods for simultaneous and quantitative isolation of mitochondrial DNA, nuclear DNA and RNA from mammalian cells - Nakhle, Jean; Özkan, Tülin; Lněničková, Kateřina; Briolotti, Philippe; Vignais, Marie-Luce (BioTechniques, 2020)
The aim of this study was to assess two protocols for their capacities to simultaneously isolate RNA, mtDNA and ncDNA from mammalian cells. We compared the Invitrogen TRIzol-based method and Qiagen DNeasy columns, using the HepG2 cell line and human primary glioblastoma stem cells. Both methods allowed the isolation of all three types of nucleic acids and provided similar yields in mtDNA. However, the yield in ncDNA was more than tenfold higher on columns, as observed for both cell types. Conversely, the TRIzol method proved more reproducible and was the method of choice for isolating RNA from glioblastoma cells, as demonstrated for the housekeeping genes RPLP0 and RPS9.
Keywords: savci; reagenční diagnostické soupravy; mitochondria; Humans; messenger RNA; Cell Nucleus; RNA; mitochondriální DNA; DNA, Mitochondrial; buněčné jádro; lidé; nádorové kmenové buňky; zvířata; Mammals; Neoplastic Stem Cells; glioblastom; Hep G2 Cells; RNA, Messenger; mitochondrial DNA (mtDNA); nuclear DNA (ncDNA); buňky Hep G2; Biochemistry; mammalian cells; Glioblastoma; Reagent Kits, Diagnostic; biochemie; Animals